The Metallurgy of the Brass Craft Industry of Muslim Mindanao - T. IGNACIO, MA. TERESA; M.CALACA , FARIDAH; C. LEYSON, JOY; S. TEJERO , BEETHOVEN (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
The production of the brass craft articles in Maguindanao and Tugaya, Lanao del Sur was studied and documented. Actual production of castings was ob:erved and artisans were interviewed. Chemical composition analysis of raw materials as well as metallographic analysis of products were conducted. The centuries old casting and foundry techniques being utilized to produce agongs, kulintangs, and betel nut boxes amnong others were handed down from one generation to another by the craftsmen. The methods were crude but workable. Most of the raw materials had chemical composition that varied within a wide range: Cu(65-88%): Zn(0-25%): Sn(0-17%): Pb(0-6%). The microstructure of theproducts also varied from the needle-alpha phase, dendritic alpha solid solution to severely cored structure.